Parental beliefs and child-rearing attitudes and mental health problems among schoolchildren - Vitolo, Ymara Lúcia Camargo; Fleitlich-Bilyk, Bacy; Goodman, Robert; Bordin, Isabel Altenfelder Santos (Revista de Saúde Pública, 2005)
OBJECTIVE: To verify the prevalence and identify the risk factors related to mental health problems among schoolchildren and its possible association with the beliefs and educational attitudes of parents/caretakers. METHODS: Cross-sectional study with a stratified probabilistic sample (n=454) of first to third-graders from public and private schools in Southeastern Brazil. Standardized instruments were administered to parents/caretakers by trained interviewers, including screening questionnaires for mental health problems among children and parents/caretakers; a questionnaire on beliefs and attitudes; and a questionnaire for socio-economic status. Chi-square tests and logistic regression models were used for statistical analysis. RESULTS: We found 35.2% prevalence of clinical/borderline cases among students. Parents/caretakers that believed in corporal punishment as a child-rearing method used physical aggression towards their children more frequently (64.8%). Logistic regression models showed that the act of hitting the child with a belt was associated to conduct problems and to overall mental health problems among schoolchildren in the presence of other risk factors: child gender (male), parents/caretakers with mental health problems, and adverse socioeconomic conditions. CONCLUSIONS: The high prevalence of mental health problems among schoolchildren and its association with child-rearing methods and mental health problems among parents/caretakers indicate the need for psycho-educational interventions aimed to reduce physical abuse and mental health problems in childhood.